Carbohydrate changes during growth and fruiting in Pleurotus ostreatus. Issue 6 (June 2016) - Zhou, Shuai; Ma, Fuying; Zhang, Xiaoyu; Zhang, Jingsong
Abstract: The carbohydrate distribution in mushrooms is reported changing greatly in its different regions during growth and fruiting. In this study, the carbohydrate distribution in the compost and fruiting bodies of Pleurotus ostreatus was analysed. Sugar, polyol, polysaccharide, and chitin content during different growth phases and in different regions of the mushroom were determined. Results indicate that trehalose, mannitol, and glucose were first accumulated in the compost and then decreased during differentiation and growth of fruiting bodies. Meanwhile, trehalose, mannitol, and glucose also accumulated in the fruiting bodies and primarily distributed in the stipe, base, and pileus region, respectively. Polysaccharides mainly accumulated within the pileus and stipe regions, and chitin was mainly observed in the base region. These findings provide insights into carbohydrate function and utilisation during mushroom growth. Highlights: Trehalose mainly distributed in the stipe at growth phase IV. Mannitol mainly distributed in the base at growth phase III. The soluble polysaccharide mainly distributed in the stipe at phase III. The soluble polysaccharide contains three major fractions. The chitin mainly distributed in the base at phase IV.